Balancing Fluency and Accuracy: A Comparative Analysis of Error Tolerance in English for Food and Beverage Service from Recruiters’ and Instructors’ Perspectives - Yuliasri, Issy; Wedhanti, Nyoman Karina; Ana, I Ketut Trika Adi (Journal of Education Reseach and Evaluation, 2025)
English communication in multilingual and multicultural environments, such as cruise ship hospitality, often presents challenges due to differences in english proficiency, first language influences, and cultural factors among the speakers involved. This study aims to compare the perspectives of two cruise ship hospitality industry stakeholders: english instructors at a job training institution and cruise ship staff recruiters, to investigate the types of speech errors tolerated in a professional environment. This study was qualitative. The subjects were three english instructors and three recruiters. Data was collected through interviews and documentation. The collected data were analyzed using thematic analysis. The study found significant differences in perspective between the two groups. On the one hand, recruiters focused on real world performance, they were more tolerant of errors as long as the message remained clear, confident, and communicative. On the other hand, english instructors emphasized grammatical accuracy, appropriate vocabulary, and correct structure, considering errors as indicators of insufficient english language competence. Thus, recruiters and English instructors have different views on errors in english communication in a professional environment.